In media we trust versus the media we trust: information subsidies and credibility of editorial content in Nigerian newspapers (2020)
The mass media serve as the forum for public discussions, political debates and the forging of consensus. However, it has been argued that media efforts to engage, empower and educate audiences are puny owing to several factors such as excessive reliance on public relations contents and well-funded agendas that dominate the media space. Media Studies in many countries have confirmed the growing reliance of journalists on Public Relations (PR) materials—also called information subsidy—but studies in Nigeria have not investigated this phenomenon and its implications for media gatekeeping and agenda-setting functions. The current study was designed to fill this gap. Agenda-setting and Gatekeeping media theories were employed as framework, while mixed methods design was adopted. From two Tier-1 newspapers (The Guardian and Punch), a total of 1,216 news stories drawn through constructed week sampling from 4-11 January 2016, the year the first Nigerian PR industry report was published, were content analysed. This study confirmed the growing reliance of Nigerian newspapers on information subsidy. This reliance on PR materials weakened the gatekeeping function of Nigerian newspapers, but did not undermine their agenda-setting function as the newspapers devoted their prominent pages (17%) to self-generated contents compared to the volume of materials PR (20.3%) confined to inner and less-prominent pages.